2017
DOI: 10.1016/j.bjid.2017.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Low seroprevalence of Zika virus in Cameroonian blood donors

Abstract: A Zika virus seroepidemiology study was performed in 1084 blood donors collected from August to October 2015 in six sites of Cameroon representing a large panel of eco-environments. Samples were tested using an anti-NS1 IgG ELISA detection kit and positives were further confirmed by seroneutralization. The observed global seroprevalence was low (around 5%, peaking at 10% and 7.7% in Douala and Bertoua, respectively) with risk factors associated with seropositivity pointing to the existence of a local (peri-)sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
90
1
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(108 citation statements)
references
References 8 publications
6
90
1
11
Order By: Relevance
“…In Bolivia the ZIKV seroprevalence among blood donors was 39.0% in Beni and 25.1% in Santa Cruz departments, 20 in Suriname it was 35.1% 21 (urban and rural population), in Nicaragua: 36.1%, 45.8% and 56.4% in pediatric, household and adult cohorts 22 respectively, while in Northeast Brazil (63.3%) (total ZIKV seroprevalence for HIV-infected, tuberculosis patients and pregnant women). 23 On the other hand, in other regions of the world the ZIKV seroprevalence among blood donors was lower or similar to our results, examples being Rwanda (1.4%) 24 , Cameroon (5%) 25 and Laos (4.5 −9.9%). 26 The difference in ZIKV seroprevalence can be explained on one Our study demonstrated a significant difference between the obtained ZIKV seroprevalence by ELISA and PRNT tests.…”
Section: Discussionsupporting
confidence: 88%
“…In Bolivia the ZIKV seroprevalence among blood donors was 39.0% in Beni and 25.1% in Santa Cruz departments, 20 in Suriname it was 35.1% 21 (urban and rural population), in Nicaragua: 36.1%, 45.8% and 56.4% in pediatric, household and adult cohorts 22 respectively, while in Northeast Brazil (63.3%) (total ZIKV seroprevalence for HIV-infected, tuberculosis patients and pregnant women). 23 On the other hand, in other regions of the world the ZIKV seroprevalence among blood donors was lower or similar to our results, examples being Rwanda (1.4%) 24 , Cameroon (5%) 25 and Laos (4.5 −9.9%). 26 The difference in ZIKV seroprevalence can be explained on one Our study demonstrated a significant difference between the obtained ZIKV seroprevalence by ELISA and PRNT tests.…”
Section: Discussionsupporting
confidence: 88%
“…In Central Africa, ZIKV circulation in human populations was confirmed in Cameroon, Central African Republic (CAR), and Gabon [18]. As an example, in Cameroon, 2 to 10% blood donors were ZIKV-positive [27]. In Central Africa, exposure to ZIKV has also been confirmed in animals, monkeys and bats [18], and ZIKV was detected in two mosquito species in CAR (Ae.…”
Section: Discussionmentioning
confidence: 99%
“…aegypti has never been found naturally infected with ZIKV in the Central African region. However, from a study with blood donors showing that ZIKV is circulating in Cameroon, nearly 5-10% of people from six towns have been exposed to ZIKV infections [27]. The vector competence of natural Aedes populations from Central Africa has remained unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, the majority of studies aiming at test validation investigated patients with acute febrile illness and included only a few or no sera from individuals living in areas where DENV is endemic, limiting the ability to extrapolate results from those studies to our study population. Recent studies investigating asymptomatic blood donors from Martinique and Cameroon suggested applicability of the NS1-based ELISA, despite a high DENV burden in these areas ( 45 , 46 ). Furthermore, our NS1-based ELISA results were largely congruent with PRNT-based analyses conducted within subpopulations.…”
Section: Discussionmentioning
confidence: 99%